Outcome of Induction of Labour in Nulliparous Women Following Replacement of Cervidil with Prostin - Abhijit Basu; Stephen Elgey; Mano Haran (The Scientific World Journal)
This study at the Logan Hospital, Australia, compared the outcome of induction of labour (IOL) in nulliparous women following replacement of Cervidil with Prostin. Eighty-two nulliparous women were identified for this retrospective cohort study over a period of three months on either side of the changed practice. Forty-four women received Prostin and 38 received Cervidil. Baseline characteristics were similar amongst the groups including maternal age, mean gestational age, and modified Bishop’s score at the commencement of IOL. The incidence of amniotomy, oxytocin augmentation of labour, and rate of epidural use did not differ significantly between the groups. The mean time to delivery (vaginally or abdominally) showed a significant difference, with women receiving Prostin delivering earlier than those having Cervidil (𝑃=0.018). Women receiving Prostin were more likely to have assisted vaginal delivery compared to the Cervidil group (𝑃=0.04).